Beware the discretionary choices of arbitrators - Gus Van Harten (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2013)
This Perspective summarizes recent research on how investment treaty arbitrators have used their power to review sovereigns. It suggests a need for more scrutiny of arbitrators' performance by other actors, such as national associations of legislators or judges.
Keywords: 330